Design and evaluation of a high concentration, high penetration unipolar corona ionizer for electrostatic discharge and aerosol charging - Panich Intra (2018)
The aim of this paper is to design and evaluate a high concentration, high penetration unipolar corona ionizer. The electrostatic characteristics in terms of voltage-current relationships of the present ionizer in the discharge zones for positive and negative coronas were discussed. Using ion current measurement, the concentration and penetration of ions were evaluated at corona voltages across the needle electrodes between 1 and 4 kV, flow rates between 1 and 5 L/min, and an operating pressure of 1 atm. In the discharge zone of the ionizer, the highest ion concentrations were found to be about 1.71×1014 and 5.09×1014 ions/m3 for positive and negative coronas, respectively. At the outlet of the ionizer, it was found that the highest ion concentration was about 1.95×1013 and 1.91×1013 ions/m3 for positive and negative coronas, respectively. The highest ion penetration for positive and negative coronas through the ionizer was found to be about 98% and 33%, respectively. The Nit product for positive and negative coronas was also found to 1.28×1013 and 7.43×1013 ions/m3s, respectively. From the findings, this ionizer proved to be particularly useful as an aerosol charger for positive and negative charge before the detector in an electrical aerosol detector.